Testing knowledge sharing effectiveness: trust, motivation, leadership style, workplace spirituality and social network embedded model - Rahman, Muhammad Sabbir; Osman-Gani, Aahad M.; Momen, Md. Abdul; Islam, Nazrul (Walter de Gruyter GmbH, 2015)
The aim of this inquiry is to investigate the relationships among the antecedents of knowledge sharing effectiveness under the position of non -academic staff of higher learning institutions through an empirical test of a conceptual model consisting of trust, extrinsic and intrinsic motivation, leadership style, workplace spirituality and online social network. This study used the respondents from the non-academic staff of higher learning institutions in Malaysia (n = 200), utilizing a self-administered survey questionnaire. The structural equation modeling approach was used to test the proposed hypotheses. The outcomes indicate that all the antecedents play a substantial function in knowledge sharing effectiveness. In addition, perceived risk plays a mediating role between trust and knowledge sharing effectiveness. On the other hand, this research also proved the communication skill also plays a mediating role between leadership style and knowledge sharing effectiveness. This study contributes to pioneering empirical findings on knowledge sharing literature under the scope of the non-academic staff perspective.